2018
DOI: 10.1002/pri.1714
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy needs for patients with physical function injuries post‐earthquake disasters: A systematic review of Chinese and Western literature

Abstract: These data can help improve earthquake disaster planning, infrastructure development, and resource needs assessment effectiveness. More prospective research study designs and more recent earthquake disasters in China are likely associated with greater explicit use of valid and reliable outcome measurements such as joint motion assessment, manual muscle testing, visual analogue pain scale, and the Barthel index or modified Barthel index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Activities of daily living were divided into five sub-categories as per need of help of caregiver(s): total dependency (score: 0), substantial help (score: 1-3), moderate help (score: 4-6), minimal help (score: 7-9), and independent (score: 10). The total score is 100 (10 Â 10) and it is categorized as 0-24: total dependency on a caregiver; 25-49: high dependency; 50-74: moderate dependency; 75-94: mild dependency; 95 or more: total independency (18).…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…Activities of daily living were divided into five sub-categories as per need of help of caregiver(s): total dependency (score: 0), substantial help (score: 1-3), moderate help (score: 4-6), minimal help (score: 7-9), and independent (score: 10). The total score is 100 (10 Â 10) and it is categorized as 0-24: total dependency on a caregiver; 25-49: high dependency; 50-74: moderate dependency; 75-94: mild dependency; 95 or more: total independency (18).…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…This is in line with recommendations for assessing pain intensity in acute pain management, such as after surgery or trauma [ 100 102 ]. Testing the AIM-T against a widely used and validated measure such as the BI adds to current literature as it has been used in similar settings [ 48 52 , 103 ]. Besides, the BI was chosen as comparator measure due to its brevity, simplicity, and affordability.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review examining the physical therapy needs for earthquake injuries within Chinese and Western literature concluded that physical therapy is crucial for treating patients with multisystem injuries, such as fractures, traumatic brain injuries, spinal cord injuries, peripheral nerve injuries, and soft tissue injuries. [11] The majority of patients sustained multiple injuries (77.3%), affecting various body parts including the extremities, head, chest, abdomen, and pelvic region, rather than a single injury, as observed in the Lushan Earthquake in China, 2015. [12] In line with the literature, our rehabilitation clinic assessed each patient for specific injuries and medical issues, implementing individualized, patient-based rehabilitation approaches based on their needs.…”
Section: Discussionmentioning
confidence: 99%